Pathways to Permanence: Legal Status Transitions as a Key Mechanism in Skilled Migrant Selection and Settlement - Jacobs, Elizabeth M. (Frontiers in Sociology, 2019)
Despite impassioned debates about immigration reform brewing in the U.S. government, researchers know remarkably little about how immigration policy shapes migration behavior. There is still much to learn about the composition of specific classes of admission, how long migrants stay in the United States, and the legal channels they follow to permanent residency or emigration. This paper takes a life course perspective on skilled migration to examine the micro-level processes and various pathways that lead to permanent settlement and emigration and identifies legal status transitions as a key sorting mechanism in processes of immigrant selection. I find that migrants who successfully underwent a previous legal status transition were more likely to pursue permanent residence, but also saw a wider array of avenues and options to obtain a green card. The mismatch in some migrants’ permanent settlement intentions and temporary legal status can lead to feelings of alienation and frustration in the immigration system and the U.S. labor market, driving some to emigrate or seek channels outside of the skilled migration program to obtain a green card. The findings of this paper deepen our understanding of the processes that shape selection effects among immigrants and highlight the need for more robust and granular longitudinal data on legal status indicators.